Analysis of 17 maize hybrids grown in 17 environments from the Highlands of Central Mexico - Reynoso Quiroga, Carlos Adolfo; González Huerta Andrés; Pérez López Delfina de Jesús; Franco Mora, Omar; Torres Flores José Luis; Velázquez Cardelas Gustavo Adrían; Breton Lugo, Carmen; Balbuena Melgarejo, Artemio; Mercado Vilchis, Omar (Revista Mexicana de Ciencias Agrícolas, 2018)
The Highlands of Central Mexico is a very important region for the production of maize (Zea mays L.) and specifically for breeding and technology for the generation of agricultural area. In this study were evaluated in demonstration and validation 17 maize hybrids in 17 environments in this region plots to identify outstanding genetic material considering its performance mainly grain, plant and ear heights and the growing cycle of the cultivars. The main results showed that the 17 hybrid material could be classified as intermediate cycle based on male blooms (87 to 97 days) and female (89.4 to 99 days). The variable most affected by the heterogeneity among the 17 environments from central Mexico was the grain yield (RG), which ranged from 2.20 (El Batán date 2) to 8.64 t (Tlaxcoapan); the difference between minor and major towns of RG was 6.44 t. Tlaxcoapan, Santa Lucía, Amealco (date 1), Boximo and Epitacio Huerta was the best locations (8.19, 8.10, 7.35 and 7.95 t) for the evaluation of the tests. H-55, regarded as the control was 6.30 t ha-1 and was only statistically surpassed by CMT 099 004 (6.90 t ha-1). Cultivars H-55, CML457 / CML459//IML-6, 099003 CMT, CMT 099 027, H-57, 0290502 CMT, CMT and Insurgentes 099 002 (from 6.1 to 6.3 t ha-1) had statistically identical RG. The previous eight hybrids represent the most outstanding to start new breeding programs or technology generation material and are also recommended for the production of certified seed or commercial planting in the study area.